Use of bone marrow aspirate concentrate (BMAC) in the treatment of delayed unions and nonunions: a single-center case series - Canton, Gianluca; Tomic, Marko; Tosolini, Luca; Di Lenarda, Luca; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Surgical treatment of delayed unions and nonunions requires adherence to the principles of mechanical stability, as well as consideration of biological environment. Bone marrow aspirate concentrate (BMAC) provides cellular and growth factor supply acting as an osteoinductive and osteogenic stimulus in bone healing. The aim of the study is to analyze the outcome of delayed unions and nonunions treatment with autologous bone marrow concentrate supplementation at our institution.Methods: Study included all patients treated at the Orthopedic and Traumatology Unit of Cattinara Hospital-ASUGI (Trieste, Italy) between September 2015 and January 2022 for delayed union or nonunion who received bone marrow aspirate concentrate (BMAC) supplementation. Initial treatment, definitive surgical treatment, radiographic healing and complications were retrospectively evaluated. Data collection was conducted by clinical database searching.Results: The study population included 11 patients, F:M 7:4, mean age 61 years. Initial treatment was surgical in 82% of patients. Radiographic healing of the fracture occurred in 100% of cases. None of the patients presented complications.Conclusions: Bone marrow aspirate concentrate (BMAC) has shown encouraging results and a high safety profile. Thus, it could be an effective and safe method in the treatment of delayed unions and nonunion. However, further studies will be needed to clarify its role.